Persepsi Penderita Hipertensi terhadap Kepatuhan Diet - Ayufrianti, Terry; Tursilowati, Susi (Poltekkes Kemenkes Semarang, 2013)
Background : Hypertension or High Blood Pressure is the major health problem in developed countries. Basic Health Research results (RISKESDAS) in Central Java (2007) showed 31,7% of Indonesia’s population suffer hypertension. According to data was taken from Semarang Health Department in 2009, there was Tlogosari Kulon village had the greatest prevalence of Hypertension ( 6,35%) .Objective : To describes perceptions of people with hypertension related adherence to dietMethod : This was a qualitative research. The research subjects namely informant I (hypertension) and II (the closest informant I). Selection of informants used purposive sampling technique with a maximal sampling variation type. The total number of informants were 12 people. The data was collected through in depth interview and observation methods using non-structure questionnaire with open-ended question . Triangulation source was used related to validite data.Results : There are informants who thinks sodium is iodized salt and foods that taste salty / savory; several informants using herbal therapies in the treatment of hypertension; all informants stated that access to get food preservation quite easily within the scope of the area; most of the informants had known about the definition, symptoms and effects of hypertension; the majority of informants have a habit of eating foods high in sodium; support officers is very helpful in providing information on all things related to hypertension and its management; family support is very helpful in controlling dietary compliance; health facilities are useful in implementing a diet because it is fast, easy and inexpensive.Conclusion : All informants perceptions about dietary compliance is in compliance with the advice of health personnel and to avoid restrictions in terms of both behavior and food consumption. Educate the public needed to be specifically about the sodium.